Pengaruh Kualitas Pelayanan Pajak, Pemahaman Peraturan Pajak Serta Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Mirawati; Nurmilah, Risma (Ikatan Da'i Indonesia, 2024)
This study explores the influence of tax service quality, understanding of tax regulations, and tax sanctions on motor vehicle taxpayer compliance in Sukabumi City. The problem phenomenon identified is the low level of motor vehicle taxpayer compliance, which has a negative impact on local tax revenue. The purpose of this study is to measure the extent to which the three variables affect taxpayer compliance. The research method used is a quantitative approach with data collection techniques in the form of questionnaires distributed to 100 respondents. Data analysis was performed using multiple linear regression. The results showed that the quality of tax services did not have a significant effect on taxpayer compliance. In contrast, understanding tax regulations and tax sanctions has a positive and significant effect on taxpayer compliance. Thus, increasing taxpayers' understanding of tax regulations and the application of effective sanctions can increase motor vehicle taxpayer compliance in Sukabumi City.